Patternable transparent and conductive elastomers towards flexible tactile/strain sensors. Issue 33 (8th August 2017) - Li, Ren'ai; Chen, Guangxue; He, Minghui; Tian, Junfei; Su, Bin
Abstract : 3D patternable, transparent, stretchable, and conductive elastomers based on the photopolymerization of the acrylic-acid/choline-chloride deep eutectic solvent were prepared, which can serve as flexible tactile/strain sensors. Abstract : Transparent conductive elastomers are an emerging platform for stretchable electronics, attractive due to their ability to sustain high physical deformations while still fulfilling optical/electrical functions. Poly(deep eutectic solvent)s (DESs) can serve as a new type of transparent conductive elastomers as a result of their low cost, green fabrication, non-toxicity and post-treatment-free advantages. Here, we report a 3D patternable (starfish type), transparent (transmittance of ∼81%), stretchable (strain up to 150%), and conductive (∼0.2 S m −1 ) elastomer based on the photopolymerization of the acrylic-acid/choline-chloride DES. The combination of transparency, elasticity, conductivity and patternability allows the poly(DES) elastomers to serve as flexible tactile/strain sensors. Our methodology has the potential to exploit the new application of poly(DESs), and opens up a new powerful route to fabricate all-organic transparent, conductive elastomers for a myriad of applications in future flexible electronics.